COP negotiations and Malaysian climate change roadmap: a comparative assessment using a dynamic environmental model - Ahmed, Adeel; Al-Amin, Abul Quasem; Rasiah, Rajah (Springer Verlag (Germany), 2019)
This study critically evaluates two COP proposals on Malaysia that have been under consideration to reduce climate damage. A top-down disaggregation framework deploying an “Empirical Regional Downscaling Dynamic Integrated Model of Climate and the Economy” is used to evaluate the local government climate roadmap and Malaysia’s emissions reduction agendas under COP21 and subsequently COP22 proposals. The findings show that the costs from climate damage over the period 2010–2110 under the Malaysian Optimal Climate Action scenario will amount to MYR5,483 (US$1589) billion. The commensurate climate damage costs under the COP21 and COP22 scenario would be MYR5, 264 (US$1526) billion. Thus, the effective proposal for reducing climate damage in Malaysia over the period 2010–2110 is the COP22 time-adjusted COP21 proposal but there are a number of macroeconomic cost implications for savings and consumption that policy makers must address before acting. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.